Aspects and challenges of unmanned aircraft systems safety assurance and certification for advanced operations - Karyotakis, Michail K.; Panagiotakopoulos, Dimitrios; Braithwaite, Graham; Tsourdos, Antonios (American Institute of Aeronautics and Astronautics (AIAA), 2021)
Like manned aviation, a Safety Management System (SMS) needs to be developed for Unmanned Aircraft Systems (UAS) taking into account their unique characteristics, and the huge variety of different operations they can perform. Towards developing a SMS for unmanned aviation this paper focuses on Safety Assurance and Certification for advanced UAS operations. Based on the manned aviation practices and the Concepts of Operations (ConOps) that have been developed for UAS, this paper examines two indicative operational scenarios (OS) in unmanned aviation identifying the gaps in the view of the safety assurance and certification processes. The findings form the basis for the proposal and development of a new safety management framework for certain UAS operations. The examination of OS shows that operation-centric operational approvals as well as faster integration of UAS to the current airspace may be possible under certain conditions.
Keywords: Air Transportation Systems